K11 C9orf72 Expansions Are The Most Common Genetic Cause Of Huntington's Disease Phenocopy Presentations In A Uk Cohort. (17th September 2014) - Hensman Moss, DJ; Poulter, M; Beck, J; Polke, JM; Campbell, T; Adamson, G; Hehir, J; Mudanohwo, E; McColgan, P; Wild, EJ; Haworth, A; Sweeney, MG; et al.
Abstract : Background: In many cases where Huntington's disease (HD) is suspected, the genetic test for HD is negative: these are known as HD phenocopies. Most of these individuals remain without a genetic diagnosis. A repeat expansion in the C9orf72 gene has been identified as the major cause of familial and sporadic frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). Aim: To determine whether the C9orf72 expansion mutation causes HD phenocopies. Methods: A cohort of 514 HD phenocopy patients were analysed for the C9orf72 expansion using repeat-primed PCR. In cases where the expansion was found, Southern hybridisation was performed to determine expansion size. Clinical case notes were reviewed to determine the phenotype of expansion-positive cases. Results: 10 subjects (1.95%) had the expansion, making it the commonest identified genetic cause of HD-phenocopy presentations. The size of expansion was not significantly different from that associated with other clinical presentations of C9orf72 expanded cases. The C9orf72 expansion-positive subjects were characterised by the presence of movement disorders including dystonia, chorea, myoclonus, tremor and rigidity. Furthermore the age of onset in this cohort was lower than previously reported for subjects with the C9orf72 expansion, and included one case with paediatric onset. Conclusions: This study extends the known phenotype of the C9orf72 expansion, both in age of onset and movement disorder symptoms. We propose a revised clinico-genetic algorithm for the investigation of HD-phenocopy patients based on these data.